WORKSHOP ASESMEN PORTOFOLIO ANAK USIA DINI BERBASIS DIGITAL UNTUK GURU PAUD KABUPATEN SERANG - Rivo Panji Yudha; Intan Yusmarini; Apriana Anggraini; Ayu Vera Dewi; Mala Komalasari; Fathkul Jannah Putri Ayuni; Erna Widiastuti; Yashinta Yashinta (Jurnal Abdimas Bina Bangsa, 2023)
This study aims to improve the ability of Early Childhood Education teachers in Serang District in conducting digital portfolio assessments in early childhood. This research uses the workshop method which consists of training stages, digital portfolio development, and evaluation. The research sample was 20 Early Childhood Education teachers in Serang District who were selected by purposive sampling. Data was collected through pre-tests, observations, and interviews. The results of the study show that digital portfolio training and development can improve teachers' abilities in conducting portfolio assessments in early childhood. This study concludes that digital-based early childhood portfolio assessment workshops are effective for increasing the ability of Early Childhood Education teachers to conduct portfolio assessments in early childhood